2019
DOI: 10.5551/jat.47043
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Change in Omentin-1 Level Correlated with Early Improvement of Myocardial Function in Patients with First Anterior ST-Segment Elevation Myocardial Infarction After Primary Percutaneous Coronary Intervention

Abstract: Aim: Omentin-1, as a novel adipocytokine, ameliorates obesity-associated disorders and suppresses the development of atherosclerotic lesions. The present research investigated the correlation between serum omentin-1 and post-infarction myocardial function.Methods: A total of 52 patients with first anterior ST-segment elevation myocardial infarction (STEMI) were recruited into this study. Participants were divided into two subgroups according to median admission omentin-1 concentration. δ1 was defined as (admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Recently, an increasing number of studies have shown that CCL20, IL1R2, and ITLN1 are correlated with MI [9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. It was also revealed that the stimulation of peripheral blood mononuclear cells by transforming growth factor-β could lead to enhanced CCL20 expression [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an increasing number of studies have shown that CCL20, IL1R2, and ITLN1 are correlated with MI [9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. It was also revealed that the stimulation of peripheral blood mononuclear cells by transforming growth factor-β could lead to enhanced CCL20 expression [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ITLN1 is expected to become an important index for evaluating the occurrence of coronary heart disease [ 43 ]. Zhu et al showed that ITLN1 can inhibit myocardial ischemia-reperfusion injury and negative remodeling associated with injury [ 25 ]. Similarly, Kadoglou et al reported that ITLN1 expression was significantly low in patients with acute MI at admission, but significantly high upon the suppression of inflammation after six months in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of studies have previously shown that CCL20, IL1R2 and ITLN1 were found to be correlated with MI(YAN et al 2012;KATAOKA et al 2014;KADOGLOU et al 2015;MENZEL et al 2016;SAFA et al 2016;STEJSKAL et al 2016;YABLUCHANSKIY et al 2016;NAGASAKA et al 2017;CHANG et al 2018;LIAN et al 2018;ORREM et al 2018;CHEN et al 2019;LIN et al 2019;ZHU et al 2019;ZHANG et al 2020). It was uncovered that the stimulation by transforming growth factor-β of peripheral blood mononuclear cells could have enhanced expression of CCL20 (LIN et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Because omentin ameliorates the myocardial damage, it was considered a cardioprotective acute phase reactant in ACS patients. High omentin levels and low CKMB levels were observed in ACS patients at the time of admission [29]. Du et al [25] demonstrated that omentin levels were lower in CAD, and the amount of omentin expression was lower in adipose tissue around the stenotic coronary artery than the adipose tissue surrounding the non-stenotic coronary artery.…”
Section: Discussionmentioning
confidence: 99%